The Competition and Regulation Are Challenges for Rurals Banks - Widyastuti, Maria; Hermanto, Y Budi; Lusy (International Journal of Psychosocial Rehabilitation, 2020)
This type of descriptive qualitative research, which aims to find out and analyze how Rurals Banks (Rurals Bank) who face challenges in the form of competition from non-bank financial institutions and commercial banks engaged in micro and Financial Services Authority Regulation (POJK) No 5 / POJK.03 / 2015 regarding the requirement for minimum capital supply. Respondents from the study were Managing Directors of Rurals Bank from four districts and cities, namely: Sidoarjo, Krian, Gresik and Surabaya. The results of in-depth interviews are known, in the face of challenges used: 1) branding strategies to build a positive image; 2) institutional strengthening and internal reform through: overcoming capital through mergers or inviting new investors; improve governance because success does not depend on the size of the business but depends on the speed in anticipating change; improve the quality of human resources with integrity where thoughts and speech must be the same, and the last to make products and services that are more varied, Ninety-nine percent are the same as competitors but one percent must be different from looking at niche markets